Graphite composite material and preparation method and application thereof

By using a metal organic framework in graphite materials to dopate with lithium and deposit amorphous carbon to form carbon nanotubes, the low energy density and expansion problems of graphite negative electrode materials are solved, and the first efficiency and cycling performance of lithium-ion batteries are improved. It is suitable for Fast charging condition.

CN119240688APending Publication Date: 2025-01-03SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411380950.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have low energy density, low first efficiency, and volume expansion during charging and discharging, making them difficult to apply to fast charging conditions and poor circulation performance.

Method used

Doping metal organic framework materials with lithium, amorphous carbon and lithium are deposited by chemical vapor deposition method, and then mixed with the graphite material to form carbon nanotubes to form efficient graphite composite materials.

Benefits of technology

The first-time efficiency, liquid retention performance, low expansion, fast charging and circulation performance of graphite composite materials are improved, the electronic conductivity and mechanical strength of the material are enhanced, and the overall performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240688A_ABST
    Figure CN119240688A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, in particular to a graphite composite material and a preparation method and application thereof. The preparation method comprises the following steps: heating metal lithium to obtain lithium steam, and depositing the lithium steam into a metal organic framework material to obtain a lithium-doped metal organic framework material; a chemical vapor deposition method is adopted, carbon source gas and oxygen are introduced, amorphous carbon is deposited in the lithium-doped metal organic framework material, and an amorphous carbon and lithium co-doped metal organic framework material is obtained; and mixing the amorphous carbon and lithium co-doped metal organic framework material, a metal salt solution and a graphite material to obtain a mixture, heating, carrying out solid-liquid separation, taking solid components, introducing carbon source gas, and reacting to generate carbon nanotubes, thereby obtaining the graphite composite material. When the prepared graphite composite material is applied to a lithium ion battery as a negative electrode material, the battery has the advantages of high first efficiency, good liquid retention performance, low expansion, fast charge, good cycle performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a graphite composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industries such as mobile phones and electric vehicles, high energy density, fast charging and long service life have become the goals pursued by secondary batteries. Graphite material is a commonly used negative electrode material in existing lithium-ion batteries. The main methods to improve the energy density of graphite are: improving the material specific capacity, compaction density and its first efficiency. The main factors affecting the material specific capacity and compaction density are the raw materials and their graphitization treatment process. The main raw materials used in existing graphite materials are needle coke and petroleum coke, and it is difficult to significantly improve their specific capacity and compaction density; the factors affecting the first efficiency are the coating material on the surface of the material and its defectivity. The main coating material of existing fast-charging graphite is soft carbon or hard carbon, which is used to improve fast charging and low-temperature performance. However, due to the low first efficiency of the coating material itself, the first efficiency of the graphite composite material will be reduced; of course, there is still a certain volume expansion problem in the graphite negative electrode during the charging and discharging process, which will seriously affect the life of the battery; the above problems also make it difficult for graphite negative electrode materials to be suitable for fast charging conditions. Metal organic framework (MOF) materials are porous framework materials with a porous structure and low expansion, but their initial efficiency is also low and their direct use effect is not good. Summary of the invention

[0003] Therefore, the purpose of the present invention is to overcome the defects of graphite negative electrode materials in the prior art, such as low energy density, low initial efficiency, volume expansion during charging and discharging, low cycle performance, and difficulty in adapting to fast charging conditions, so as to provide a graphite composite material and its preparation method and application.

[0004] To this end, the present invention provides the following technical solutions.

[0005] The present invention provides a method for preparing a graphite composite material, comprising the following steps: S1: heating metallic lithium to obtain lithium vapor, depositing the lithium vapor into a metal organic framework material to obtain a lithium-doped metal organic framework material; S2: using a chemical vapor deposition method, introducing carbon source gas and oxygen, depositing amorphous carbon in the lithium-doped metal organic framework material to obtain amorphous carbon and lithium co-doped metal organic framework material; S3: mixing the amorphous carbon and lithium co-doped metal organic framework material, a metal salt solution and a graphite material to obtain a mixture, heating, solid-liquid separation, taking a solid component, introducing a carbon source gas, reacting to generate carbon nanotubes, and obtaining a graphite composite material. Optionally, in step S1, the heating temperature is 1000-1400°C, and the vacuum degree is ≤0.1Mpa; for example, the vacuum degree can be 0.01-0.1MPa.

[0006] Optionally, in step S1, the mass ratio of the metal organic framework material to metallic lithium is 100:1-5.

[0007] Optionally, in step S1, the metal organic framework compound includes at least one of a magnesium-based metal organic framework compound, a nickel-based metal organic framework compound, a manganese-based metal organic framework compound, and a cobalt-based metal organic framework compound.

[0008] In the preparation method of the graphite composite material provided by the present invention, lithium vapor is obtained after heating metallic lithium, and the step of depositing the lithium vapor into the metal organic framework material can specifically be that a metal organic framework compound (MOF) is added to the middle of a vacuum furnace, metallic lithium is spread flat on the bottom, and the lithium vapor generated by heating rises into the MOF material, so that the metallic lithium is deposited in the pores of the MOF.

[0009] Optionally, in step S2, the temperature of chemical deposition is 700-900° C., and the time is 30-300 min.

[0010] Optionally, in step S2, the volume ratio of the carbon source gas to oxygen is 10:1-3.

[0011] Optionally, in step S2, the total flow rate of the carbon source gas and oxygen is 100 to 500 sccm.

[0012] Optionally, in step S2, the ratio of the metal organic framework compound to the carbon source gas in terms of carbon mass is 100:10-40.

[0013] Optionally, in step S3, the mass ratio of the graphite material, the amorphous carbon and lithium co-doped metal organic framework material, and the metal salt is 100:5-15:1-5.

[0014] Optionally, in step S3, the mass concentration of the metal salt solution is 1% to 10%.

[0015] Optionally, in step S3, the heating temperature is 100-200° C. and the heating time is 1-6 hours.

[0016] Optionally, in step S3, the reaction temperature is 900-1200° C. and the reaction time is 30-300 min.

[0017] Optionally, in step S3, the flow rate of the carbon source gas is 10 to 50 sccm.

[0018] Optionally, in step S3, the ratio of the mass of the solid component to the mass of carbon in the carbon source gas is 100:2-10.

[0019] Optionally, in step S3, the metal salt includes at least one of ferric chloride, nickel chloride, cobalt chloride, ferric nitrate, nickel nitrate, and ferric nitrate.

[0020] Optionally, in step S3, the graphite material includes at least one of artificial graphite and natural graphite.

[0021] Optionally, in step S3, the solid-liquid separation method includes any one of filtration and centrifugation.

[0022] Optionally, in step S3, the particle size of the graphite material is 5 to 15 μm.

[0023] Optionally, in step S2 or step S3, the carbon source gas includes at least one of methane, ethane, ethylene, and acetylene.

[0024] Optionally, step S3 further includes the step of adding a dispersant to the mixture; optionally, the mass ratio of the graphite material to the dispersant is 100:1-5; further optionally, the dispersant includes at least one of sodium polystyrene sulfonate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate. Sodium polystyrene sulfonate can be a conventional sodium polystyrene sulfonate material with a commercial average molecular weight of 50,000 to 100,000.

[0025] Optionally, the step S3 further includes the step of adding an organic ligand to the mixture; optionally, the mass ratio of the graphite material to the organic ligand is 100:1-5; further optionally, the organic ligand includes at least one of imidazole, 2-methylimidazole, and bifonazole. When the step S3 includes the step of adding an organic ligand to the mixture, a chemical reaction occurs during heating, and the amino group in the organic ligand combines with the hydroxyl group or carboxyl group in the metal organic framework material to form a network structure.

[0026] The invention also provides a graphite composite material prepared by the preparation method.

[0027] The present invention provides a negative electrode plate, comprising the above graphite composite material.

[0028] The present invention also provides a lithium-ion battery, comprising the above-mentioned negative electrode plate, a positive electrode plate, a separator and an electrolyte.

[0029] In summary, the beneficial effects achieved by the present invention are:

[0030] The preparation method of the graphite composite material provided by the present invention comprises the following steps: S1: heating metallic lithium to obtain lithium vapor, and depositing the lithium vapor into a metal organic framework material to obtain a lithium-doped metal organic framework material; S2: using a chemical vapor deposition method, introducing carbon source gas and oxygen, and depositing amorphous carbon in the lithium-doped metal organic framework material to obtain amorphous carbon and lithium co-doped metal organic framework material; S3: mixing the amorphous carbon and lithium co-doped metal organic framework material, a metal salt solution and a graphite material to obtain a mixture, heating, solid-liquid separation, taking solid components, introducing carbon source gas, reacting to generate carbon nanotubes, and obtaining a graphite composite material. First, metallic lithium is deposited into the pores of the metal organic framework material, and then amorphous carbon is deposited in the lithium-doped metal organic framework material using carbon source gas and oxygen by chemical deposition to obtain amorphous carbon and lithium co-doped metal organic framework material, and then heated to make the amorphous carbon and lithium co-doped metal organic framework material, metal salt and graphite material mixed and attached together, and then the carbon source gas is introduced to react to generate carbon nanotubes, wherein the metal salt acts as a catalyst in the subsequent reaction of generating carbon nanotubes. The preparation method has high preparation efficiency, controllable process, and can make the doped material highly consistent. When the obtained graphite composite material is used as a negative electrode material in a lithium-ion battery, the battery has the advantages of high initial efficiency, good liquid retention performance, low expansion, fast charging and good cycle performance. Among them, after lithium doping, in the process of depositing amorphous carbon in the metal organic framework material by chemical vapor deposition using carbon source gas and oxygen, the carbon source gas generates amorphous carbon and deposits in the amorphous carbon, and the oxygen causes the lithium exposed on the surface of the undeposited amorphous carbon to form lithium oxide, which plays a role in passivating lithium, meeting the safety of subsequent processing while improving the cycle performance and rate performance of the battery. Metal organic framework compounds can help reduce the expansion of the battery during charging and discharging, carbon nanotubes can improve the electronic conductivity of the material, and its high mechanical strength can help restrain the expansion of graphite during charging and discharging. Lithium doping with carbon nanotubes can also reduce the irreversible capacity of carbon nanotubes, improve the electronic and ionic conductivity of the material, and improve fast charging and cycle performance.

[0031] In the preparation method provided by the present invention, step S3 further comprises the step of adding a dispersant to the mixture. The dispersant can improve the dispersibility of the metal salt solution in the metal organic framework material co-doped with amorphous carbon and lithium on the one hand; on the other hand, the material included in the dispersant contains sulfonate groups, has a high lithium ion solvation ability, and can improve the insertion and extraction rate of the material ions.

[0032] The preparation method provided by the present invention further comprises the step of adding an organic ligand to the mixture in step S3. The amino group in the organic ligand will combine with the hydroxyl group or carboxyl group in the metal organic framework material, cross-link to form a network structure, further improve the structural stability of the material, and thus improve the cycle performance. At the same time, the organic ligand can also improve the interface structure and improve the dispersion performance of the material, and improve the strength of the graphite composite material after carbonization, helping to improve the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a SEM image of the graphite composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0037] Experimental reagents

[0038] Mg-MOF: Henan Chenglongyi New Material Technology Co., Ltd.; Model: Mg-MOF-74;

[0039] Ni-MOF: Henan Chenglongyi New Materials Technology Co., Ltd.; Model: Ni-MOF-74;

[0040] Mn-MOF: Xi'an Ruixi Biotechnology Co., Ltd.; Model: Mn-MOF;

[0041] Lithium metal: Tianjin Zhongneng Lithium Industry Co., Ltd.;

[0042] Graphite material: artificial graphite; Shanghai Shanshan Technology Co., Ltd.; Model: EMG-P.

[0043] Example 1

[0044] This embodiment provides a method for preparing a graphite composite material, which specifically comprises the following steps:

[0045] (1) Add 100g of Mg-MOF material to the middle of a vacuum furnace, spread 3g of metallic lithium on the bottom, evacuate to 0.01Mpa, heat to 1200℃ to generate lithium vapor that rises and deposits in the pores of Mg-MOF; then cool to 800℃, and perform chemical vapor deposition at normal pressure, introduce acetylene / oxygen mixed gas (volume ratio, acetylene: oxygen = 10:3), with a total flow rate of 300sccm of mixed gas, and continue to introduce for 150min to obtain amorphous carbon and lithium co-doped MOF material. Among them, the carbon content in the introduced carbon source gas is calculated using: the total flow rate of the introduced mixed gas × the proportion of carbon source gas in the mixed gas × the density of the carbon source gas × the carbon content of the carbon source gas, the same below. Here, the carbon content in the introduced acetylene gas is 37.38g, and the carbon content in the Mg-MOF material: acetylene gas is 100:37.38.

[0046] (2) Add 10 g of amorphous carbon and lithium co-doped MOF material to 50 g of 5% ferric chloride aqueous solution, then add 3 g of sodium polystyrene sulfonate, 100 g of artificial graphite, and 3 g of imidazole, react at a temperature of 150°C for 3 h, filter, and obtain solid components and waste liquid.

[0047] (3) Take 100g of solid components and transfer them to a tube furnace and heat them to 1100°C. Then, introduce ethylene gas at a flow rate of 30sccm for 150min to react and generate carbon nanotubes to obtain the graphite composite material. The carbon content in the introduced carbon source gas is calculated by: volume of introduced carbon source gas × density of carbon source gas × carbon content percentage of carbon source gas, and the same applies below. Here, the carbon content in the introduced ethylene gas is 4.82g; the solid component mass: carbon content in the ethylene gas is 100:4.8.

[0048] Example 2

[0049] This embodiment provides a method for preparing a graphite composite material, which specifically comprises the following steps:

[0050] (1) 100g Ni-MOF material was added to the middle of a vacuum furnace, 1g metallic lithium was spread flat on the bottom, the vacuum was evacuated to 0.01Mpa, and the mixture was heated to 1000℃ to generate lithium vapor that rose and deposited in the pores of Ni-MOF; then the temperature was lowered to 700℃, and chemical vapor deposition was performed at normal pressure, with acetylene / oxygen mixed gas (volume ratio, acetylene: oxygen = 10:1) introduced, the total flow rate of the mixed gas was 100sccm, and the continuous introduction time was 300min, to obtain amorphous carbon and lithium co-doped MOF material. The carbon content in the introduced acetylene gas was 29.45g, and the carbon content in the Ni-MOF material: acetylene gas was 100:29.45.

[0051] (2) Add 5 g of amorphous carbon and lithium co-doped MOF material to 100 g of 1% nickel chloride aqueous solution, then add 1 g of sodium dodecyl sulfate, 100 g of artificial graphite, and 1 g of 2-methylimidazole, react at a temperature of 100° C. for 6 h, and filter to obtain solid components and waste liquid.

[0052] (3) 79.5 g of the solid component was transferred to a tube furnace and heated to 900° C., and acetylene gas was introduced at a flow rate of 10 sccm for 300 min to react and generate carbon nanotubes to obtain the graphite composite material. The carbon content of the introduced acetylene gas was 3.24; the solid component mass: the carbon content of the acetylene gas was 100:4.1.

[0053] Example 3

[0054] This embodiment provides a method for preparing a graphite composite material, which specifically comprises the following steps:

[0055] (1) 100g of Mn-MOF material was added to the middle of a vacuum furnace, 5g of metallic lithium was spread flat on the bottom, the vacuum was evacuated to 0.1Mpa, and the mixture was heated to 1400℃ to generate lithium vapor that rose and deposited in the pores of Mn-MOF; then the temperature was lowered to 900℃, and chemical vapor deposition was performed at normal pressure, with acetylene / oxygen mixed gas (volume ratio, acetylene: oxygen = 10:3) introduced, the total flow rate of the mixed gas was 100sccm, and the continuous introduction time was 300min, to obtain amorphous carbon and lithium co-doped MOF material. The carbon content in the introduced acetylene gas was 24.92g, and the carbon content in the Mn-MOF material: acetylene gas was 100:24.92.

[0056] (2) 15 g of amorphous carbon and lithium co-doped MOF material was added to 50 g of 10% mass concentration of cobalt chloride aqueous solution, followed by 5 g of sodium dodecylbenzene sulfonate, 100 g of artificial graphite, and 5 g of bifonazole. The mixture was reacted at 200 °C for 1 h and filtered to obtain solid components and waste liquid.

[0057] (3) 8.1 g of the solid component was transferred to a tube furnace and heated to 1200° C., and methane gas was introduced at a flow rate of 50 sccm for 30 min to react and generate carbon nanotubes to obtain the graphite composite material. The carbon content of the introduced methane gas was 0.81 g; the mass of the solid component: the mass of the carbon content of the methane gas was 100:10.

[0058] Example 4

[0059] This embodiment provides a graphite composite material and a preparation method thereof. Compared with the embodiment 1, the only difference is that the organic ligand imidazole is not added in step (2), and the rest is the same as the embodiment 1.

[0060] Example 5

[0061] This embodiment provides a graphite composite material and a preparation method thereof. Compared with Embodiment 1, the only difference is that the dispersant sodium polystyrene sulfonate is not added in step (2).

[0062] Example 6

[0063] This embodiment provides a method for preparing a graphite composite material, which specifically comprises the following steps:

[0064] (1) 100g of Mg-MOF material was added to the middle of a vacuum furnace, 5g of metallic lithium was spread flat on the bottom, and the vacuum was evacuated to 0.01Mpa. The material was heated to 1400℃ to generate lithium vapor that rose and deposited in the pores of Mg-MOF. The temperature was then lowered to 900℃, and chemical vapor deposition was performed at normal pressure. An acetylene / oxygen mixed gas (volume ratio, acetylene: oxygen = 10:1) was introduced, with a total flow rate of 500sccm and a continuous introduction time of 30min to obtain amorphous carbon and lithium co-doped MOF material. The carbon content in the introduced acetylene gas was 14.73g, and the carbon content in the Mg-MOF material: acetylene gas was 100:14.73.

[0065] (2) 15 g of amorphous carbon and lithium co-doped MOF material was added to 10 g of 10% ferric chloride aqueous solution, followed by 5 g of sodium polystyrene sulfonate, 100 g of artificial graphite, and 5 g of imidazole. The mixture was reacted at 100 °C for 6 h and filtered to obtain solid components and waste liquid.

[0066] (3) 75 g of the solid component was transferred to a tube furnace and heated to 1200° C. Ethylene gas was introduced at a flow rate of 50 sccm for 30 min to react and generate carbon nanotubes to obtain the graphite composite material. The carbon content in the introduced ethylene gas was 1.61 g; the solid component mass: the carbon content in the ethylene gas was 100:2.1.

[0067] Comparative Example 1

[0068] This comparative example provides a graphite composite material and a preparation method thereof, which is different from Example 1 only in that metal lithium is not deposited in step (1);

[0069] Step (1) is specifically as follows: 100g of Mg-MOF material is added to a vacuum furnace, the temperature is raised to 800°C, and chemical vapor deposition is performed under normal pressure, acetylene / oxygen mixed gas (volume ratio, acetylene: oxygen = 10:3) is introduced, the temperature is 450°C, the total flow rate of the mixed gas is 300SCCM, and the continuous introduction time is 150min to obtain an amorphous carbon-doped MOF material. The carbon content in the introduced acetylene gas is 37.38g, and the carbon content in the Mg-MOF material: acetylene gas is 100:37.38.

[0070] Comparative Example 2

[0071] This comparative example provides a graphite composite material and a preparation method thereof. Compared with Example 1, the only difference is that in step (2), no ferric chloride aqueous solution is used, and only an equal amount of deionized water is used.

[0072] Comparative Example 3

[0073] This comparative example provides a method for preparing a graphite composite material, which specifically comprises the following steps:

[0074] (1) Add 100g of Mg-MOF material to the middle of a vacuum furnace, spread 3g of metallic lithium on the bottom, evacuate to 0.01Mpa, heat to 1200°C to generate lithium vapor that rises and deposits in the pores of Mg-MOF to obtain a lithium-doped MOF material. Take 100g of lithium-doped MOF material and mix it evenly with 5g of asphalt, heat it to 250°C to melt it, and then heat it to 900°C to carbonize it for 3h to obtain an amorphous carbon-coated lithium-doped MOF material;

[0075] (2) 10 g of amorphous carbon-coated lithium co-doped MOF material was added to 50 g of deionized water, followed by 3 g of sodium polystyrene sulfonate, 100 g of artificial graphite, and 3 g of imidazole. The mixture was reacted at 150 °C for 3 h and filtered to obtain a solid component and waste liquid.

[0076] (3) 100 g of the solid component was transferred to a tube furnace and heated to 1100° C. Ethylene gas was introduced at a flow rate of 30 sccm for 150 min to react and generate carbon nanotubes, thereby obtaining the graphite composite material.

[0077] Test Example 1

[0078] The graphite composite material obtained in Example 1 was observed under SEM, and the image is as follows Figure 1 As shown, it can be seen that the material presents a secondary granular structure with a particle size between 10 and 15 μm.

[0079] Test Example 2

[0080] The interlayer spacing D002 and specific surface area of ​​the graphite (002) crystal plane of the graphite composite materials in the examples and comparative examples were tested according to the test method in the standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries". The diffusion coefficient of the powder material was tested by constant current intermittent titration technique (GITT), and the resistivity of the powder was tested using a four-probe tester.

[0081] The graphite composite materials in the embodiment and the comparative example are respectively assembled into button cells according to the following method: the graphite composite material is used to make a negative electrode plate, and the negative electrode plate is assembled into a button cell with a lithium plate, an electrolyte and a diaphragm in a glove box with an argon gas and a water content of less than 0.1ppm. The preparation method of the negative electrode plate is as follows: the graphite composite material, the conductive carbon black SP and the binder PVDF are dispersed in a solvent deionized water according to a mass ratio of 96.5:1:2.5 and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and the single-side surface density is 6mg / cm 2 After baking and rolling, the negative electrode sheet is obtained. The separator is celegard 2400; the electrolyte is a LiPF6 solution, in which the concentration of LiPF6 is 1 mol / L, and the solvent is a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a weight ratio of 1:1.

[0082] The performance of the button cell was tested using a blue electric tester. The test conditions were: 0.1C charge and discharge rate, voltage range 0.005 ~ 2V, stop after 3 cycles, and then test its discharge capacity under 0.1C conditions, i.e. T1; then charge the button cell at 0.1C rate to 5mV, then discharge at 2C rate to 2V, and get the discharge capacity T2, and calculate the rate performance of 2C / 0.1C. Rate performance = T2 / T1×100%.

[0083] First efficiency and first discharge specific capacity test: Charge the battery to 0.005V at 1C, record the first charge specific capacity, then discharge it to 2V, record the first discharge specific capacity, and calculate the first efficiency, first efficiency = first discharge specific capacity / first charge specific capacity × 100%.

[0084] Cyclic performance test method: At 25±3℃, first charge to 2V at 0.2C, then discharge to 0.005V at 0.2C, cycle the above charging and discharging steps for 100 weeks, and calculate the capacity retention rate after 100 weeks.

[0085] The full-charge expansion rate of the negative electrode plate: First, the thickness of the negative electrode plate after rolling is tested to be D1; and the button battery is lithium-intercalated at a rate of 0.1C until it is terminated at 5mV. The button battery is dissected and the thickness of the negative electrode plate is tested to be D2. The full-charge expansion rate is (D2-D1) / D1×100%.

[0086] All the test results above are shown in Tables 1 and 2.

[0087] Table 1 Electrical properties of button cells

[0088]

[0089]

[0090] Table 2 Electrical properties of button cells

[0091]

[0092] It can be seen from Tables 1 and 2 that the resistivity, first efficiency and diffusion coefficient of the graphite composite material prepared in the embodiment are significantly better than those in the comparative example. The reason is that the carbon nanotubes doped in the material improve the electronic conductivity of the material and the doped metal lithium is converted into lithium ions during the charge and discharge process to improve the lithium ion transmission rate of the material, thereby improving the diffusion coefficient and the first efficiency of the material.

[0093] Test Example 3

[0094] The negative electrode sheet was made of the graphite composite material prepared in the embodiment and the comparative example, and was assembled into a 5Ah soft-pack battery with the positive electrode sheet made of the positive electrode active material ternary material, the electrolyte and the separator.

[0095] The preparation method of the positive electrode sheet is as follows: the positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) was dispersed in solvent NMP with conductive carbon black SP and binder PVDF in a mass ratio of 97:1.5:1.5 and mixed evenly to obtain positive electrode slurry. The positive electrode slurry was evenly coated on one side of the positive electrode current collector aluminum foil with a single-side surface density of 20 mg / cm 2 After baking and rolling, the positive electrode sheet is obtained.

[0096] The preparation method of the negative electrode sheet is as follows: disperse the graphite composite material, conductive carbon black SP and binder PVDF in a mass ratio of 96.5:1:2.5 in solvent deionized water and mix them evenly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and the single-side surface density is 9.5 mg / cm 2After baking and rolling, the negative electrode sheet was obtained. The separator is celegard 2400, and the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.1 mol / L). The cycle performance and fast charging performance of the soft pack battery are tested, and the test results are detailed in Table 3.

[0097] (1) Cycle performance: The battery was tested for 500 cycles at a charge / discharge rate of 1C / 1C, a voltage range of 2.8V to 4.2V, and a temperature of 25±3°C.

[0098] (2) Fast charging performance: Charge at a constant current rate of 2C to 4.2V, and charge at a constant voltage for 2h at 4.2V to reach 100% SOC (full charge state). Then calculate the constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity).

[0099] Table 3 Electrical properties of soft pack batteries

[0100]

[0101] It can be seen from Table 3 that the cycle performance and fast charging performance of the soft-pack battery prepared by the graphite composite material obtained in each embodiment are significantly better than those of Comparative Examples 1 to 3. The reason is that the surface of the graphite composite material obtained in the embodiment is coated with lithium-doped MOF, which can reduce the liquid retention performance of the expansion-enhancing material and improve the cycle performance; at the same time, the embodiment material has a high diffusion coefficient and a low powder resistivity, which can improve the fast charging performance. Moreover, in Examples 1, 2, 3, and 6, since dispersants and organic ligands are added during the preparation process to help improve the dispersion performance of the material and improve the interface structure of the metal organic framework material, it can be seen that the cycle performance is further improved compared with Example 4 without the use of organic ligands and Example 5 without the use of dispersants. Compared with the embodiment, no metallic lithium is deposited in Comparative Example 1, no metal salt is used in the preparation of Comparative Example 2, and no amorphous carbon-coated lithium-doped MOF material is prepared by the method specified in this application in Comparative Example 3, and the cycle performance and fast charging performance are both deteriorated, which proves that the graphite composite material prepared by the preparation method specified in this application has good performance.

[0102] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the present invention.

Claims

1. A method for preparing a graphite composite material, characterized in that: The steps include: S1: heating metallic lithium to obtain lithium vapor, and depositing the lithium vapor into a metal organic framework material to obtain a lithium-doped metal organic framework material; S2: using a chemical vapor deposition method, introducing a carbon source gas and oxygen to deposit amorphous carbon in the lithium-doped metal organic framework material to obtain a metal organic framework material co-doped with amorphous carbon and lithium; S3: Mixing amorphous carbon and lithium co-doped metal organic framework materials, metal salt solutions and graphite materials to obtain a mixture, heating and solid-liquid separation, taking solid components, introducing carbon source gas, reacting to generate carbon nanotubes, and obtaining a graphite composite material.

2. The preparation method according to claim 1, characterized in that: In step S1, the heating temperature is 1000-1400°C and the vacuum degree is ≤0.1MPa; and / or, the mass ratio of the metal organic framework material to the metallic lithium is 100:1 to 5; And / or, the metal organic framework compound includes at least one of a magnesium-based metal organic framework compound, a nickel-based metal organic framework compound, a manganese-based metal organic framework compound, and a cobalt-based metal organic framework compound.

3. The preparation method according to claim 1 or 2, characterized in that: In step S2, the temperature of chemical deposition is 700-900°C and the time is 30-300 minutes; and / or, the volume ratio of the carbon source gas to oxygen is 10:1-3; and / or, the total flow rate of the carbon source gas and oxygen is 100 to 500 sccm; And / or, the ratio of the metal organic framework compound to the carbon source gas in terms of carbon mass is 100:10-40.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S3, the mass ratio of the graphite material, the amorphous carbon and lithium co-doped metal organic framework material, and the metal salt is 100:5-15:1-5; and / or, the mass concentration of the metal salt solution is 1% to 10%; and / or, the heating temperature is 100 to 200° C. and the heating time is 1 to 6 hours; And / or, the reaction temperature is 900-1200°C and the reaction time is 30-300 min; and / or, the flow rate of the carbon source gas is 10 to 50 sccm; and / or, the ratio of solid component mass: carbon content in the carbon source gas is 100:2-10; And / or, the metal salt includes at least one of ferric chloride, nickel chloride, cobalt chloride, ferric nitrate, nickel nitrate, and ferric nitrate; And / or, the graphite material includes at least one of artificial graphite and natural graphite; And / or, the solid-liquid separation method includes any one of filtration and centrifugation.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S2 or S3, the carbon source gas includes at least one of methane, ethane, ethylene, and acetylene.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The step S3 also includes the step of adding a dispersant to the mixture; optionally, the mass ratio of the graphite material to the dispersant is 100:1-5; further optionally, the dispersant includes at least one of sodium polystyrene sulfonate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The step S3 also includes the step of adding an organic ligand to the mixture; optionally, the mass ratio of the graphite material to the organic ligand is 100:1-5; further optionally, the organic ligand includes at least one of imidazole, 2-methylimidazole, and bifonazole.

8. A graphite composite material obtained by the preparation method according to any one of claims 1 to 7.

9. A negative electrode plate, characterized in that: The graphite composite material comprises the graphite composite material as claimed in claim 8.

10. A lithium ion battery, characterized in that: It includes the negative electrode plate as described in claim 9, and also includes a positive electrode plate, a separator and an electrolyte.

Citation Information

Cited By

  • Gradient lithium concentration pre-lithiation negative electrode based on directional temperature control and dynamic atmosphere regulation and control

    CN120356899A

  • Carbon negative electrode material and preparation method thereof, negative electrode plate, electrochemical device and electronic equipment

    CN121553941A

  • A carbon negative electrode material and a preparation method thereof, a negative electrode sheet, an electrochemical device, and an electronic device

    CN121553941B